Universal Classification System and FID - Ranganathan, S. R.; Neelameghan, A. (Journal of Information and Knowledge, 2000)
The major ideas emerging from the FID/CR Seminar on UDC in a Mechanised Retrieval System, convened in 1968 in Copenhagen are mentioned. The implications of a universal classification system and the use of electronic machinery in a system for document finding are examined. The attributes of the universe of subjects and the psychology of readers are considered as the major factors influencing the design of a system for document finding. The need for a General Theory of Classification constituted out a hierarchy of general normative principles, laws of library science, and postulates, canons and principles for classification form the national foundation for the design and use in practice of a universal classification system. The capacity of UDC for being developed into a universal classification system are examined from this point of view. The different statements contained in the FID/CR Report about the particular attributes of UDC for its development as a universal of scheme for classification are examined from the angle of intrinsic and adventitious merits of a classification system. Concludes with suggestions about the need for change in attitude and about the new role of FID as an international organisation promoting the development of a world information network based on a universal classification system.